Kecerdasan Buatan sebagai Co-Counselor dalam Bimbingan dan Konseling: Tantangan dan Peluang di Indonesia - Nur, Edil Wijaya; Zulfikri (ILIN Education Indonesia, 2025)
The development of artificial intelligence (AI) has significantly impacted various sectors, including guidance and counseling (GC) services. This study aims to explore the challenges and opportunities in implementing AI as a co-counselor within GC services in Indonesia, particularly at the secondary education level. A descriptive qualitative approach was employed, using literature review as the primary method. Data sources included scientific articles, policy documents, and relevant research findings, which were thematically analyzed. The results indicate that AI implementation in GC offers potential to improve service efficiency, broaden access to counseling, and support personalized interventions based on data. However, key challenges include ethical concerns, data privacy, AI’s limited understanding of local cultural nuances, and the readiness of human resources (counselors and school guidance teachers) to adopt such technology. The study concludes that AI can serve as an effective co-counselor when integrated thoughtfully, ethically, and contextually. Strategic policies, continuous professional development for GC practitioners, and the development of AI systems that are responsive to local values and students’ psychosocial needs are essential for successful implementation.